Inca cusqueña ceramics: Variety in its shapes and designs - Villacorta Oviedo, Yanet (2021)
Inca-style ceramics have various decorative shapes and motifs, and their distribution provides valuable information to study the expansion of the Inca state. After Rowe's initial work in 1944, limited work was carried out in Cusco to illuminate the nature of the variants in Inca ceramics. In this document, I compile the existing information and argue that the Inca ceramic assembly of Cusco should be analyzed and classified more comprehensively, including a broader analysis of morphological and iconographic attributes. Therefore, I will present the results of my work and discuss the nature of more than 121 varieties in 18 morphological classes and their distribution in Cusco.